All-solid-state secondary battery
By designing the layout of composite solid electrolytes and insulating components in an all-solid-state secondary battery, the problem of physical defects in the short circuit and process of the battery is solved, and higher safety and cycling characteristics are achieved.
Patent Information
- Application Number
- CN202110995464.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-08-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-08-27
AI Technical Summary
Existing all-solid-state lithium-ion batteries are prone to overheating and ignition in short circuit situations, and are prone to physical defects and short circuits during the pressing process and the punching process.
An all-solid state secondary battery design adopts a new structure, including a positive electrode layer, a negative electrode layer, a first solid electrolyte layer and a second solid electrolyte layer, a composite solid electrolyte at the center of the second solid electrolyte layer, and an insulating member at the periphery of the second solid electrolyte layer, through which physical defects during the pressing and punching process are reduced.
Effectively reduces the occurrence of short circuits during the charging/discharging process, improves the cycle characteristics and safety of the battery, and avoids the risks of overheating and ignition.
Smart Images

Figure CN114122506B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2020-0109484 filed in the Korean Intellectual Property Office on August 28, 2020, the entire contents of which are incorporated herein by reference. Technical Field
[0003] One or more aspects of embodiments of the present disclosure relate to an all-solid-state secondary battery. Background Art
[0004] In recent years, batteries with increased energy density and high safety have been actively developed in accordance with industrial needs. For example, lithium-ion batteries have been put into practical use in the automotive industry and information-related equipment and communication equipment. In the automotive industry, safety and reliability are important due to their relationship with driver and traffic safety.
[0005] Currently commercialized lithium-ion batteries use an electrolyte solution containing a flammable organic dispersion medium (e.g., one or more flammable solvents), and therefore when a short circuit occurs, there is a possibility of overheating and / or ignition. As a result, all-solid-state batteries using solid electrolytes instead of electrolyte solutions have been proposed.
[0006] Since all-solid-state batteries do not use flammable organic solvents, the possibility of overheating and / or catching fire can be greatly reduced even when a short circuit occurs. Therefore, compared with lithium-ion batteries using electrolyte solutions, such all-solid-state batteries can greatly enhance safety. Summary of the invention
[0007] One or more aspects of the embodiments of the present disclosure relate to an all-solid-state secondary battery of a new structure.
[0008] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the embodiments presented in the disclosure.
[0009] One or more embodiments of the present disclosure provide an all-solid-state secondary battery, comprising:
[0010] a positive electrode layer; a negative electrode layer; a first solid electrolyte layer between the positive electrode layer and the negative electrode layer and adjacent to the positive electrode layer; and a second solid electrolyte layer between the positive electrode layer and the negative electrode layer and adjacent to the negative electrode layer,
[0011] wherein the positive electrode layer includes a positive electrode collector and a positive electrode active material layer on the positive electrode collector, the negative electrode layer includes a negative electrode collector and a first negative electrode active material layer or a third negative electrode active material layer on the negative electrode collector, and the composite solid electrolyte and the insulating member are located between the first solid electrolyte layer and the second solid electrolyte layer, and
[0012] wherein the composite solid electrolyte is on a central portion of the second solid electrolyte layer and includes an ion conductor and a lithium salt, and the insulating member is on a peripheral portion of the second solid electrolyte layer and adjacent to or around one or more (e.g., all) outer surfaces of the composite solid electrolyte (e.g., surrounding one or more (e.g., all) outer surfaces of the composite solid electrolyte). BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The above and other aspects, features and advantages of certain embodiments of the present disclosure will become more apparent from the following description taken in conjunction with the accompanying drawings, in which:
[0014] Figure 1 is a cross-sectional view of an all-solid-state secondary battery according to an embodiment;
[0015] Figure 2A A schematic diagram for explaining a process for preparing an all-solid-state secondary battery according to an embodiment;
[0016] Figure 2B To explain Figure 2A Schematic diagram of insulating members L1 and L2 of an all-solid-state secondary battery;
[0017] Figure 3 is a schematic diagram of an upper surface of a composite structure according to an embodiment;
[0018] Figure 4 is a cross-sectional view of an all-solid-state secondary battery according to another embodiment; and
[0019] Figure 5 is a cross-sectional view of an all-solid-state secondary battery according to another embodiment. DETAILED DESCRIPTION
[0020] The embodiment in the accompanying drawings will now be explained in more detail with reference to its embodiment, wherein the same reference numerals refer to the same elements throughout the text, and its repeated description may not be provided. In this regard, the present embodiment may have different forms, and should not be interpreted as being limited to the description stated herein. Accordingly, the following is merely to describe the embodiment with reference to the accompanying drawings to explain the aspects of this description. As used herein, the term "and / or" includes any and all combinations of one or more related enumerated items. Statements such as "at least one of ... ", "one of ... " and "selected from ... " modify the elements of the entire list when before / after the list of elements, and do not modify the single element of the list.
[0021] As used herein, singular forms such as "a", "an", and "the" are intended to include plural forms as well, unless the context clearly indicates otherwise. It will be further understood that the terms "includes", "including", "comprises", and / or "comprising", when used in this specification, specify the presence of recited features, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, steps, operations, elements, components, and / or groups thereof.
[0022] As used herein, the terms "use", "using" and "used" may be considered synonymous with the terms "utilize", "utilizing" and "utilized", respectively. Further, the use of "may" when describing embodiments of the present disclosure refers to "one or more embodiments of the present disclosure".
[0023] It will be understood that when an element is referred to as being "on," "connected to," or "coupled to" another element, it can be directly on, connected to, or coupled to the other element, or one or more intervening elements may also be present. When an element is referred to as being "directly on," "directly connected to," or "directly coupled to" another element, there are no intervening elements.
[0024] For ease of description, spatially relative terms such as "below," "beneath," "below," "above," "upper," "bottom," and "top," etc., may be used herein to describe the relationship of one element or feature to another element(s) or feature(s) as illustrated in the accompanying drawings. It will be understood that spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientation depicted in the accompanying drawings. For example, if the device in the accompanying drawings is turned over, elements described as being "below" or "beneath" other elements or features will be oriented "above" or "on" the other elements or features. Thus, the term "below" may encompass both orientations of above and below. The device may be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein should be interpreted accordingly.
[0025] Hereinafter, an all-solid-state secondary battery according to one or more embodiments will be described in more detail.
[0026] The all-solid-state secondary battery including a sulfide solid electrolyte in the art requires pressing under high pressure. The all-solid-state secondary battery in the art is prepared as follows: the positive electrode layer, the solid electrolyte layer and the negative electrode layer are laminated, and the laminate of these layers is pressed under high pressure. When a flat press is applied in the pressing of the laminate, due to the step difference (e.g., height difference) between the positive electrode layer and the solid electrolyte layer, physical defects may occur at the edge (e.g., peripheral edge) of the solid electrolyte layer during the blanking process, and due to the defects, during the initial charging process, current may flow between the negative electrode and the positive electrode.
[0027] When an all-solid-state secondary battery is manufactured according to this method, many physical defects may occur on the fracture surface generated in the punching process. During the initial charging process, the defects may cause a short circuit.
[0028] Since the sulfide-based solid electrolyte becomes brittle after pressing, when a separate pressing process is additionally applied, the battery including the sulfide-based solid electrolyte may have additional physical defects or existing defects may further develop.
[0029] In this regard, the inventors have completed the present disclosure and provide an all-solid-state secondary battery having a structure that can solve these problems to fundamentally eliminate the physical defects of the fracture surface generated during the pressing process and the blanking process so that the defects and their effects can be reduced (e.g., may not be displayed) during the charging / discharging process.
[0030] All-solid-state secondary battery
[0031] According to an embodiment, an all-solid-state secondary battery includes a positive electrode layer; a negative electrode layer; a first solid electrolyte layer between the positive electrode layer and the negative electrode layer and adjacent to the positive electrode layer; and a second solid electrolyte layer between the positive electrode layer and the negative electrode layer and adjacent to the negative electrode layer, wherein the positive electrode layer includes a positive electrode collector, and a positive electrode active material on the positive electrode collector, and the negative electrode layer includes a negative electrode collector, and a first negative electrode active material layer or a third negative electrode active material layer on the negative electrode collector.
[0032] The all-solid-state secondary battery may include a composite structure between a first solid electrolyte layer and a second solid electrolyte layer. The composite structure may include a composite solid electrolyte, which is on the central portion of the second solid electrolyte layer and includes an ion conductor and a lithium salt; and an insulating member, which is arranged on the outer periphery of the second solid electrolyte layer and adjacent to one or more (e.g., all) outer surfaces of the composite solid electrolyte or around one or more (e.g., all) outer surfaces of the composite solid electrolyte (e.g., surrounding one or more (e.g., all) outer surfaces of the composite solid electrolyte).
[0033] When the composite structure between the first solid electrolyte layer and the second solid electrolyte layer includes a composite solid electrolyte on the central portion of the second solid electrolyte layer; and an insulating member surrounding the outer surface of the composite solid electrolyte and arranged on the outer periphery of the second solid electrolyte layer, the defects of the solid electrolyte layer generated during the pressing process and the punching process can be less likely to occur or be reduced, and thus the short circuit between the positive electrode and the negative electrode can be prevented or reduced. In particular, the rapid reduction of the battery capacity due to the short circuit can be prevented or reduced, and thus the cycle characteristics of the all-solid-state secondary battery can be improved.
[0034] Thermoplastic adhesive coating may be on one or more surfaces of insulating member. When the thermoplastic adhesive coating is on the surface of insulating member, the insulating member may be bonded to the composite solid electrolyte, for example, bonded to one or more side surfaces of the composite solid electrolyte layer, so that the bonding strength can be well maintained, and / or the bonding strength of the insulating member and the first solid electrolyte layer and / or the second solid electrolyte layer may be enhanced. The fluidity and / or wetting ability of the insulating member may be high, and therefore the insulating member may be well absorbed and impregnated (for example, to another surface or element) without voids or gaps, to have excellent or suitable viscosity, for example, even on the uneven surface of the solid electrolyte layer or despite the internal defects of the solid electrolyte layer. When the fluidity of the insulating member is low, the wetting ability of the insulating member may be degraded, and the permeability for the rough surface may be low, which makes it difficult for the insulating member to be attached to the first solid electrolyte layer or the second solid electrolyte layer without defects.
[0035] The composite solid electrolyte and the insulating member are between the first solid electrolyte layer on the positive electrode layer and the second solid electrolyte layer on the negative electrode layer, which produces a reduced interface resistance.
[0036] The positive electrode layer having the first solid electrolyte layer thereon was laminated on the composite solid electrolyte / insulating member on the second solid electrolyte layer, and then the layers were hot pressed, thereby preparing an all-solid-state secondary battery.
[0037] refer to Figure 1 , the all-solid-state secondary battery 1 includes a positive electrode layer 10; a negative electrode layer 20; and a first solid electrolyte layer 13 and a second solid electrolyte layer 23 between the positive electrode layer 10 and the negative electrode layer 20. The first solid electrolyte layer 13 is adjacent to (i.e., closer to) the positive electrode layer 10, and the second solid electrolyte layer 23 is adjacent to (i.e., closer to) the negative electrode layer 20.
[0038] The composite solid electrolyte 30 and the insulating member 31 are between the first solid electrolyte layer 13 and the second solid electrolyte layer 23, as shown in FIG. Figure 1 When the thickness of the composite solid electrolyte 30 and the thickness of the insulating member 31 are substantially the same, the composite solid electrolyte 30 will not be visible in the cross-sectional view. Figure 1 , the thickness of the composite solid electrolyte 30 is exaggerated to illustrate the arrangement state (eg, positioning) of the composite solid electrolyte 30 .
[0039] The composite solid electrolyte 30 is arranged on the central portion of the second solid electrolyte layer 23, and the insulating member 31 is arranged on the outer peripheral portion of the second solid electrolyte layer 23. The insulating member 31 may extend to the end (e.g., perimeter) or outermost portion of the second solid electrolyte layer 23. When the insulating member 31 extends at least to the end of the second solid electrolyte layer 23, cracks occurring at the end may be suppressed or reduced. As mentioned herein, the end of the second solid electrolyte layer 23 is the outermost portion of the second solid electrolyte layer 23 and may contact (e.g., be adjacent to) the side (e.g., thickness direction) surface of the second solid electrolyte layer 23. For example, the insulating member 31 may extend to the outermost portion of the second solid electrolyte layer 23, which contacts the side surface of the second solid electrolyte layer 23. In some embodiments, the insulating member 31 may be arranged to protrude from the outermost portion of the first solid electrolyte layer 13 and / or the second solid electrolyte layer 23 (e.g., exceed the outermost portion of the first solid electrolyte layer 13 and / or the second solid electrolyte layer 23), such as Figure 1 As described above, when the insulating member 31 is arranged to protrude from the outermost portion, orientation deviation (eg, misalignment) of the positive electrode layer 10 and the negative electrode layer 20 may be reduced.
[0040] The area (e.g., plane area or area in a plan view) of the composite solid electrolyte 30 may be greater than the area (e.g., plane area or area in a plan view) of the insulating member 31. When the insulating member 31 is arranged to surround the outer surface of the composite solid electrolyte 30, the area error (e.g., area mismatch) of the first solid electrolyte layer 13 and the second solid electrolyte layer 23 may be corrected. When the area error is corrected in this manner, cracks of the first solid electrolyte layer 13 and the second solid electrolyte layer 23 that occur due to the pressure difference during the pressing process may be effectively suppressed or reduced, and the orientation deviation of the positive electrode layer 10 and the negative electrode layer 20 may be reduced.
[0041] Figure 3 Schematic perspective view for explaining the composite structure 40 bonded to the second solid electrolyte layer / negative electrode layer laminate.
[0042] refer to Figure 3 , the composite structure 40 may include a composite solid electrolyte 30 and an insulating member 31 arranged to surround the outer surface of the composite solid electrolyte 30 (eg, the insulating member 31 may frame the composite solid electrolyte). Figure 3 , S1 represents the total area (e.g., plane area) of the composite solid electrolyte 30, and the total area (e.g., plane area) of the insulating member 31 is the total area of S2 and S3. Here, S3 represents the area of the insulating member 31 protruding from the outermost portion of the second solid electrolyte layer 23 (e.g., exceeding the outermost portion of the second solid electrolyte layer 23). Figure 3 The area within the middle dashed line may correspond to a lamination position (eg, perimeter) of the second solid electrolyte layer 23 .
[0043] In one embodiment, based on the total area S1+S2 corresponding to the second solid electrolyte layer 23, the area S1 of the composite solid electrolyte 30 may be less than about 100%, about 50% or greater to less than about 100%, about 50% to about 98%, about 60% to about 96%, or in the range of about 70% to about 95%, about 80% to about 95%, or about 80% to about 90%. Here, the total area of the second solid electrolyte layer 23 may be the same as the total area S1+S2. When the area S1 of the composite solid electrolyte 30 is within these ranges, short circuits caused by physical contact between the positive electrode layer 10 and the negative electrode layer 20 during the pressing process and the blanking process, or short circuits caused by overcharging of lithium, can be prevented or reduced.
[0044] An area S2+S3 of the insulating member 31 may be in a range of about 5% to about 60%, about 10% to about 40%, or about 10% to about 20%, based on the total area S1+S2 corresponding to the second solid electrolyte layer 23 .
[0045] In some embodiments, the area S2 of the insulating member 31 may be, for example, less than about 18%, less than about 10%, or in the range of about 1% to about 10%, 2% to 8%, or 4% to 6%, based on the total area S1+S2 of the second solid electrolyte layer 23. And, based on the total area S1+S2 of the second solid electrolyte layer 23, the area S3 of the insulating member 31 may be about 10% or less or in the range of about 3% to about 10% or about 4% to about 10%. When the areas S2 and S3 of the insulating member 31 are within these ranges, a short circuit caused by physical contact of the positive electrode layer 10 and the negative electrode layer 20 during the pressing process and the blanking process, or a short circuit caused by overcharging of lithium, can be prevented or reduced.
[0046] The thickness of the composite solid electrolyte 30 may be in the range of about 1 μm to about 10 μm, for example, about 2 μm to about 8 μm or about 4 μm to about 6 μm, and the thickness of the insulating member 31 may be in the range of about 1 μm to about 10 μm, for example, about 2 μm to about 8 μm or about 4 μm to about 6 μm. When the thickness of the composite solid electrolyte 30 and the insulating member 31 is within these ranges, the initial capacity and / or high rate performance of the all-solid-state secondary battery 1 may be excellent or suitable, and the processing performance and / or energy density of the all-solid-state secondary battery 1 may be improved.
[0047] The thickness of the composite solid electrolyte 30 may be controlled or selected with respect to the thickness of the insulating member 31. When the thickness of the insulating member 31 is greater than the thickness of the composite solid electrolyte 30 (e.g., significantly greater, such as 3 μm or 5 μm greater), the contact resistance may increase (e.g., because a gap may be generated between the composite solid electrolyte 30 and one of the first solid electrolyte layer 13 and the second solid electrolyte layer 23). In some embodiments, the thickness of the composite solid electrolyte 30 and the insulating member 31 may be substantially the same, for example, may differ by 2 μm or less.
[0048] Further, when the thickness of the insulating member 31 is greater than the above range, the battery processing performance can be improved, but the energy density may be poor. When the thickness of the insulating member 31 is too thin (e.g., less than the above range), the energy density may increase, but the processing performance may be poor. The thickness of the insulating member 31 may be selected (e.g., simultaneously) in consideration of processing performance and energy density. When the thickness of the composite solid electrolyte 30 is greater than the above range, a gap may occur at the edge (e.g., the edge of the laminate), and physical defects may easily occur during the contraction and expansion of the charge / discharge of the battery. When the thickness of the composite solid electrolyte 30 is thinner than the range, the interface resistance of the first solid electrolyte layer 13 and the second solid electrolyte layer 23 may increase, which may weaken the single cell performance of the battery.
[0049] Positive electrode layer: positive electrode current collector
[0050] The positive electrode current collector 11 may be a plate or foil formed of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or any alloy thereof. In some embodiments, the positive electrode current collector 11 may not be provided.
[0051] The positive electrode current collector 11 may further include a carbon layer arranged on one surface or two (e.g., all) surfaces of the metal substrate. When the carbon layer is additionally included on the metal substrate, the corrosion of the metal substrate by the solid electrolyte in the positive electrode layer 10 can be prevented or reduced, and the interface resistance between the positive electrode active material layer 12 and the positive electrode current collector 11 can be reduced. The thickness of the carbon layer may be, for example, in the range of about 1 μm to about 5 μm. When the thickness of the carbon layer is within this range, the contact between the metal substrate and the solid electrolyte can be reduced, and in some embodiments, the contact between the metal substrate and the solid electrolyte can be substantially or completely prevented without degrading the energy density of the all-solid-state secondary battery 1. The carbon layer may include amorphous carbon and / or crystalline carbon.
[0052] Positive electrode layer: positive electrode active material
[0053] The positive electrode active material layer 12 may include, for example, a positive electrode active material, a solid electrolyte, and a binder.
[0054] The positive electrode active material layer 12 may further include a conductive agent. The conductive agent may be, for example, at least one selected from graphite, carbon black, acetylene black, carbon nanofibers, and carbon nanotubes.
[0055] The solid electrolyte in the positive electrode layer 10 may be the same as or different from the solid electrolyte in the solid electrolyte layer. The details of the solid electrolyte are the same as those defined with reference to the solid electrolyte layer.
[0056] The positive electrode active material is a positive electrode active material that can reversibly absorb and desorb lithium ions. The positive electrode active material may be, for example, a lithium transition metal oxide (e.g., lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM)); lithium manganate; lithium iron phosphate; nickel sulfide; copper sulfide; lithium sulfide; iron oxide; and / or vanadium oxide, but the embodiment is not limited thereto, and any suitable positive electrode active material in the art may be used. The positive electrode active material may be a single one of these examples, or a mixture of at least two of these examples.
[0057] The positive electrode active material may be, for example, a compound represented by one of the following formulae: Li a A 1-b B' b D 2 (where 0.90≤a≤1 and 0≤b≤0.5); Lia E 1-b B' b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5, and 0≤c≤0.05); LiE 2- b B' b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Co b B' c O 2-α F' 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c O 2-α F' 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E c G d O 2(where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O 2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NeG b O 2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a CoG b O 2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a MnG b O 2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a Mn 2 G b O 4 (where 0.90≤a≤1 and 0.001≤b≤0.1); QO 2 ;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (where 0≤f≤2); Li (3-f) Fe 2 (PO 4 ) 3 (where 0≤f≤2); and LiFePO 4In the compound, A may be nickel (Ni), cobalt (Co), manganese (Mn) or a combination thereof; B' may be aluminum (Al), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), iron (Fe), magnesium (Mg), strontium (Sr), vanadium (V), a rare earth element or a combination thereof; D may be oxygen (O), fluorine (F), sulfur (S), phosphorus (P) or a combination thereof; E may be cobalt (Co), manganese (Mn) or a combination thereof; F' may be fluorine (F), sulfur (S), phosphorus (P) or a combination thereof ; G may be aluminum (Al), chromium (Cr), manganese (Mn), iron (Fe), magnesium (Mg), lanthanum (La), cerium (Ce), strontium (Sr), vanadium (V) or a combination thereof; Q may be titanium (Ti), molybdenum (Mo), manganese (Mn) or a combination thereof; I' may be chromium (Cr), vanadium (V), iron (Fe), scandium (Sc), yttrium (Y) or a combination thereof; and J may be vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu) or a combination thereof. The compounds may each independently have a surface coating (hereinafter, also referred to as a "coating"). In some embodiments, a mixture of a compound without a coating and a compound with a coating may be used, the compound being independently selected from the compounds listed above. In some embodiments, the coating may include a compound of at least one coating element selected from the group consisting of oxides, hydroxides, oxyhydroxides, oxycarbonates and hydroxycarbonates of the coating element. In some embodiments, the compound used for the coating may be amorphous and / or crystalline. In some embodiments, the coating element in the coating may be or include magnesium (Mg), aluminum (Al), cobalt (Co), potassium (K), sodium (Na), calcium (Ca), silicon (Si), titanium (Ti), vanadium (V), tin (Sn), germanium (Ge), gallium (Ga), boron (B), arsenic (As), zirconium (Zr) or a mixture thereof. In some embodiments, when a compound of the coating element is used, the coating may be formed using any method that does not adversely affect the physical properties of the positive active material. For example, a coating may be formed using a spraying method or an immersion method. The coating method may be well understood by those of ordinary skill in the art, and therefore a detailed description thereof will not be provided.
[0058] The positive electrode active material may include, for example, a lithium salt of a transition metal oxide having a layered rock salt structure among examples of lithium transition metal oxides. For example, the term "layered rock salt structure" refers to a structure in which oxygen atom layers and metal atom layers are alternately and regularly arranged in the <111> direction of a cubic rock salt structure, where each atom layer forms a two-dimensional plane. The term "cubic rock salt structure" refers to a crystal structure of the sodium chloride (NaCl) type, in which face-centered cubic (fcc) lattices formed by anions and cations, respectively, are offset by only half of the ridge of each unit lattice. Examples of lithium transition metal oxides having a layered rock salt structure may include ternary lithium transition metal oxides (such as, LiNi x Co y Al z O 2 (NCA) and / or LiNi x Co y Mn z O 2 (NCM), where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1). When the positive electrode active material includes a ternary lithium transition metal oxide having a layered rock salt structure, the energy density and / or thermal stability of the all-solid-state secondary battery 1 can be improved.
[0059] The positive electrode active material may be covered with a coating as described above. The coating may be any suitable material that can be used as a coating for the positive electrode active material of the all-solid-state secondary battery 1 in the art. The coating may be, for example, Li 2 O-ZrO 2 (LZO).
[0060] When the positive electrode active material includes a nickel (Ni)-containing ternary lithium transition metal oxide (such as, NCA and / or NCM), the capacity density of the all-solid-state secondary battery 1 increases, and thus metal dissolution from the positive electrode active material in the charged state can be reduced. As a result, the all-solid-state secondary battery 1 according to the embodiment may have improved cycle characteristics in the charged state.
[0061] The particle shape of the positive electrode active material may be, for example, a true spherical shape, an oval shape, and / or a spherical shape. The particle size of the positive electrode active material is not particularly limited, but may be within the range applicable to the positive electrode active material of the all-solid-state secondary battery 1. The amount of the positive electrode active material in the positive electrode layer 10 is not particularly limited and may be within the range applicable to the positive electrode layer 10 of the all-solid-state secondary battery 1.
[0062] Positive electrode layer: Solid electrolyte
[0063] The positive electrode active material layer 12 may include, for example, a solid electrolyte. The solid electrolyte in the positive electrode layer 10 may be the same as or different from the solid electrolyte in the first solid electrolyte layer 13. The details of the solid electrolyte may be the same as those defined with reference to the first solid electrolyte layer 13.
[0064] The average particle size D50 of the particles of the solid electrolyte included in the positive electrode active material layer 12 may be less than (e.g., smaller than) the average particle size D50 of the particles of the solid electrolyte of the first solid electrolyte layer 13. For example, the average particle size D50 of the solid electrolyte in the positive electrode active material layer 12 may be, for example, about 90% or less, about 80% or less, about 70% or less, about 60% or less, about 50% or less, about 40% or less, about 30% or less, or about 20% or less of the average particle size D50 of the solid electrolyte in the first solid electrolyte layer 13.
[0065] Positive electrode layer: Binder
[0066] The positive active material layer 12 may include a binder. Examples of the binder may include styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, and / or polymethyl methacrylate.
[0067] Positive electrode layer: Conductive agent
[0068] The positive active material layer 12 may include a conductive agent. The conductive agent may be or include, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon tube (eg, carbon nanotube) and / or metal powder.
[0069] Positive electrode layer: additives
[0070] The positive electrode active material layer 12 may further include one or more additives (eg, fillers, coating agents, dispersants, and / or ion conductive agents) in addition to the positive electrode active material, the solid electrolyte, the binder, and / or the conductive agent.
[0071] The filler, coating agent, dispersant, and / or ion conductive agent that may be included in the positive electrode active material layer 12 may be any appropriate material used for an electrode of the all-solid-state secondary battery 1 in the art.
[0072] The first solid electrolyte layer and the second solid electrolyte layer
[0073] Solid electrolyte layer: solid electrolyte
[0074] The first solid electrolyte layer 13 and the second solid electrolyte layer 23 may each independently include a solid electrolyte.
[0075] The solid electrolyte may be, for example, a sulfide-based solid electrolyte. The sulfide-based solid electrolyte may be at least one selected from the following: Li2 SP 2 S 5 , Li 2 SP 2 S 5 -LiX (wherein X is a halogen), Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are each positive numbers, and Z is one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (wherein p and q are each positive numbers, and M is one of P, Si, Ge, B, Al, Ga or In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7-x PS6-x I x (where 0≤x≤2). The sulfide-based solid electrolyte can be prepared, for example, by: 2 S and / or P 2 S 5 ) is melted and quenched or mechanically ground. Subsequently, the resultant may be heat treated. The sulfide-based solid electrolyte may be amorphous or crystalline, or may be a mixed form thereof. In some embodiments, the sulfide-based solid electrolyte may be a material selected from these examples of sulfide-based solid electrolytes including at least sulfur (S), phosphorus (P) and lithium (Li) as component elements. For example, the sulfide-based solid electrolyte may be a material including Li 2 SP 2 S 5 Here, when Li 2 SP 2 S 5 When the material is used as a sulfide solid electrolyte material, Li 2 S and P 2 S 5 The mixing molar ratio (Li 2 S:P 2 S 5 ) may, for example, be in the range of about 50:50 to about 90:10.
[0076] The sulfide-based solid electrolyte may include, for example, an argyrodite-type (eg, argyrodite-based) solid electrolyte represented by Formula 1:
[0077] Formula 1
[0078] Li + 12-n-x A n+ X 2- 6-x Y - x .
[0079] In Formula 1, A may be P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb and / or Ta, X may be S, Se and / or Te, and Y may be Cl, Br, I, F, CN, OCN, SCN and / or N 3 , 1≤n≤5, and 0≤x≤2.
[0080] The sulfide-based solid electrolyte may be, for example, a material selected from Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6- x Br x(where 0≤x≤2) and Li 7-x PS 6-x I x (wherein 0≤x≤2) is at least one of the following: 6 PS 5 Cl, Li 6 PS 5 Br and Li 6 PS 5 I is at least one argyrodite-type compound.
[0081] The density of the argyrodite-type solid electrolyte may be in the range of about 1.5 g / cc to about 2.0 g / cc. When the density of the argyrodite-type solid electrolyte is about 1.5 g / cc or higher, the internal resistance of the all-solid-state secondary battery 1 may be reduced, and / or the penetration of the solid electrolyte layer by the migration of Li may be effectively suppressed or reduced.
[0082] The elastic modulus (e.g., Young's modulus) of the sulfide-based solid electrolyte may be, for example, about 35 GPa or less, about 30 GPa or less, about 27 GPa or less, about 25 GPa or less, or about 23 GPa or less. The elastic modulus (e.g., Young's modulus) of the sulfide-based solid electrolyte may be, for example, in the range of about 10 GPa to about 35 GPa, about 10 GPa to about 25 GPa, or about 10 GPa to about 23 GPa. When the sulfide-based solid electrolyte has an elastic modulus within these ranges, the temperature and / or pressure required for sintering can be reduced, and thus the sintering of the solid electrolyte can be easily performed.
[0083] First solid electrolyte layer and second solid electrolyte layer: binder
[0084] The first solid electrolyte layer 13 and the second solid electrolyte layer 23 may each independently include, for example, a binder. The binder may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene, but the embodiment is not limited thereto, and any material that can be used as a binder in the art may be used. The binder of the first solid electrolyte layer 13 and the second solid electrolyte layer 23 may be the same as or different from the binder of the positive electrode active material layer 12 and the negative electrode active material layer 22.
[0085] Composite structure
[0086] The insulating member 31 may be disposed on the outer peripheral portion of the second solid electrolyte layer 23 and contact the composite solid electrolyte 30. At least one surface, for example, both surfaces of the insulating member 31 may be coated with a thermoplastic adhesive film.
[0087] The thermoplastic adhesive film may include a thermoplastic resin exhibiting adhesive properties.
[0088] Examples of thermoplastic resins may include appropriate thermoplastic adhesive resins (e.g., polyethylene resins, polypropylene resins, propylene-ethylene block or reduction resins, random resins, graft polymers, polystyrene resins, and / or acrylic resins). The binder may be or include a single one of these examples or a mixture of at least two of these examples. Examples of polyethylene resins may include polyolefin resins (e.g., low-density polyethylene, linear low-density polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-1-octene copolymers, ethylene-methyl acrylate copolymers, ethylene-methyl methacrylate copolymers, ethylene-vinyl acrylate copolymers, ethylene-ethyl acrylate copolymers, and / or ethylene-vinyl alcohol copolymers).
[0089] Examples of polystyrene-based resins may include AB-type diblock polymers (e.g., styrene butadiene (SB), styrene isoprene (SI), styrene ethylene-butylene copolymer (SEB) and / or styrene ethylene-propylene copolymer (SEP)), ABA-type triblock polymers (e.g., styrene butadiene styrene (SBS), styrene isoprene styrene (SIS), hydrogenated styrene butadiene styrene copolymer (SEBS) and / or hydrogenated styrene isoprene styrene copolymer (SEPS)), ABAB-type tetrablock or higher multiblock polymers, styrene-based random copolymers (e.g., styrene butadiene rubber (SBR)), and ABC-type styrene olefin crystalline block polymers (e.g., styrene ethylene-butylene copolymer olefin crystalline (SEBC)).
[0090] The composite solid electrolyte 30 may include an ion conductor and a lithium salt. The composite solid electrolyte 30 may reduce interface resistance. The composite solid electrolyte 30 may further include at least one selected from a binder and an ionic liquid.
[0091] The ion conductor may be a polymer capable of dissolving a lithium salt, and examples of the ion conductor may include polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polystyrene-acrylonitrile copolymer, polyvinyl chloride, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene vinyl acetate copolymer, and any combination thereof. The movement of lithium in the composite solid electrolyte 30 may occur in the form of intra-polymer chain, inter-chain, and / or ion cluster hopping.
[0092] The lithium salt may be, for example, selected from LiPF 6 , LiBF 4 、LiCF3 SO 3 、Li(CF 3 SO 2 ) 2 N、Li(CF 3 SO 2 ) 3 C. LiC 2 F 5 SO 3 、Li(FSO 2 ) 2 N, LiC 4 F 9 SO 3 、LiN(SO 2 CF 2 CF 3 ) 2 、LiN(CN) 2 and at least one of the compounds represented by Formulae 1 to 4. In some embodiments, the concentration of the lithium salt may be in a range of about 0.01M to about 5M, for example, about 0.1M to about 3M or about 0.1M to about 2M.
[0093]
[0094] The composite solid electrolyte 30 of the composite structure may further include a binder.
[0095] Examples of the binder may include vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene, and mixtures thereof, and / or styrene butadiene rubber-based polymers.
[0096] In some embodiments, the composite solid electrolyte 30 may be arranged closer to or adjacent to the first solid electrolyte layer 13 (e.g., closer to or adjacent to the positive electrode layer 10) than to the second solid electrolyte layer 23 and the negative electrode layer 20. When the composite solid electrolyte 30 is arranged closer to the second solid electrolyte layer 23, the thickness of the second solid electrolyte layer 23 is relatively thinner than that of the first solid electrolyte layer 13, and thus a short circuit caused by lithium dendrites may easily occur.
[0097] In the composite solid electrolyte 30, EO / Li determines the amount of lithium ions in the composite solid electrolyte 30. EO / Li represents a molar ratio of ethylene oxide (EO) to lithium in the ion conductor. EO / Li may be, for example, in the range of about 5 to about 25. When EO / Li is within this range, the ion conductivity of the composite solid electrolyte 30 may be excellent or suitable, and the precipitation of the lithium salt may be reduced or properly controlled, thereby preventing or reducing film non-uniformity and / or short circuits caused by the growth of lithium dendrites.
[0098] Because the insulating member 31 surrounds the side surface of the composite solid electrolyte 30, on the outer periphery of the second solid electrolyte layer 23, and contacts the first solid electrolyte layer 13, physical defects that may occur during the pressing process and the blanking process of the electrode plate can be reduced or eliminated. In addition, the insulating member 31 can control or reduce the lithium dendrite phase growth at the edge of the electrode plate and / or the secondary defects of the solid electrolyte layer caused by the lithium dendrite phase growth, and thus the short circuit of the all-solid-state secondary battery 1 can be suppressed or reduced.
[0099] The insulating member 31 may extend to the end (edge) or the outermost portion of the second solid electrolyte layer 23 .
[0100] The insulating member 31 may be formed of any material that does not affect the performance of the battery cell and can alleviate the defects of the solid electrolyte layer that will otherwise be generated during the punching process and prevent or reduce the short circuit of the negative electrode layer 20 and the positive electrode layer 10. The insulating member 31 may be at least one selected from an insulating polymer and an insulating inorganic material. Examples of insulating polymers may include polypropylene, polyethylene, acrylonitrile-butadiene rubber (NBR), styrene butadiene rubber (SBR), isobutylene isoprene rubber (IRR), chloroprene rubber, ethylene propylene diene monomer (EPDM) and any combination thereof. In some embodiments, the insulating member 31 may be impregnated with a lithium salt or an ionic liquid.
[0101] The area S3 of the insulating member 31 can solve the defects of the solid electrolyte layer while reducing the irreversible positive electrode loss, and can correct the orientation deviation of the positive electrode layer 10 and the negative electrode layer 20 and the area mismatch between the first solid electrolyte layer 13 and the second solid electrolyte layer 23. For example, the area S3 of the protruding portion of the insulating member 31 may be about 110% or less, about 100% or less, about 90% or less, about 80% or less, or about 70% or less of the area S2 of the insulating member 31. When the area S3 of the protruding portion of the insulating member 31 is within these ranges, the possibility of a short circuit caused by physical contact between the positive electrode active material layer 12 and the negative electrode active material layer 22 and / or the possibility of a short circuit caused by overcharging of lithium can be reduced.
[0102] exist Figure 3In the embodiment of the present invention, the area S2 of the insulating member 31 is about 20% or less or about 10% or less of the area S1. For example, in the total area of the insulating member 31, the area S2 is in the range of about 1% to about 20%, about 5% to about 20%, or about 5% to about 15% of the area S1. When the area of the insulating member 31 extends widely to the total area of the second solid electrolyte layer 23 (for example, greater than the above range), a short circuit may not occur, but the capacity of the battery may be reduced. And, when the insulating member 31 is not included in the battery, the battery may be inoperable due to the occurrence of a short circuit. The sum of the area S2 and the area S1 may be the same as the area of the second solid electrolyte layer 23.
[0103] Negative electrode layer
[0104] Negative electrode layer: negative electrode active material
[0105] The negative electrode layer 20 may include a negative electrode collector 21 and a negative electrode active material layer 22 on the negative electrode collector 21. The negative electrode active material layer 22 may include, for example, a negative electrode active material and a binder.
[0106] The negative electrode active material in the negative electrode active material layer 22 may be in the form of, for example, particles. The average particle size of the negative electrode active material may be, for example, about 4 μm or less, about 2 μm or less, about 1 μm or less, or about 900 nm or less. The average particle size of the negative electrode active material may be, for example, in the range of about 10 nm to about 4 μm, about 10 nm to about 2 μm, or about 10 nm to about 900 nm. When the average particle size of the negative electrode active material is within these ranges, the reversible absorption and / or desorption of lithium during the charge / discharge process may be further facilitated. The average particle size of the negative electrode active material may be a median particle size (D50) measured by, for example, a laser diffraction particle size distribution analyzer.
[0107] When a carbon-based negative electrode active material such as carbon black is used as the negative electrode active material, the primary particle size of the carbon-based negative electrode active material is 10 nm to 900 nm.
[0108] The negative electrode active material may include, for example, at least one selected from a carbon-based negative electrode active material and a metal or metalloid negative electrode active material.
[0109] The carbon-based negative electrode active material may be, for example, amorphous carbon. Examples of amorphous carbon may include carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), and / or graphene, but the embodiment is not limited thereto, and any amorphous carbon available in the art may be used. The term "amorphous carbon" refers to carbon that has no crystallinity or has very low crystallinity, and is distinguished from (e.g., different from) crystalline carbon or graphite carbon.
[0110] The metal or metalloid negative electrode active material may include at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn), but the embodiment is not limited thereto, and any metal negative electrode active material or metalloid negative electrode active material in the art that can form an alloy or compound with lithium can be used. For example, nickel (Ni) does not form an alloy with lithium and therefore may not be used as a metal negative electrode active material.
[0111] For example, the negative electrode active material layer 22 may include one of the negative electrode active materials listed above or a mixture of the above multiple negative electrode active materials. For example, the negative electrode active material layer 22 may include only amorphous carbon alone, or may include at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn). In some embodiments, the negative electrode active material layer 22 may include amorphous carbon and a mixture of at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn). In the mixture of amorphous carbon and, for example, gold (Au), the mixing ratio of amorphous carbon to gold (Au) may be, for example, about 10:1 to about 1:2, about 5:1 to about 1:1, or about 4:1 to about 2:1, but the embodiment is not limited thereto, and the mixing ratio may be appropriately selected according to desired or appropriate characteristics of the all-solid-state secondary battery 1. When the negative active material of the negative active material layer 22 has the composition as described above, the all-solid-state secondary battery 1 may have further improved cycle characteristics.
[0112] The negative electrode active material of the negative electrode active material layer 22 may include, for example, a mixture of first particles including amorphous carbon (e.g., composed of amorphous carbon) and second particles including metal or metalloid (e.g., composed of metal or metalloid). Examples of metals or metalloids may include gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn). For example, the metalloid may be a semiconductor. Based on the total weight of the mixture, the amount of the second particles may be in the range of about 8 weight % (wt%) to about 60 wt%, about 10 wt% to about 50 wt%, about 15 wt% to about 40 wt%, or about 20 wt% to about 30 wt%. When the amount of the second particles is within these ranges, the all-solid-state secondary battery 1 may have further improved cycle characteristics.
[0113] Negative electrode layer: Binder
[0114] Examples of the binder in the negative electrode active material layer 22 may include, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile and / or polymethyl methacrylate, but the embodiment is not limited thereto, and any material that can be used as a binder in the art may be used. The binder may be formed of a single one or more different binders from these examples of the binder.
[0115] When the negative electrode active material layer 22 includes a binder, the negative electrode active material layer 22 may be stable on the negative electrode collector 21. Also, cracks in the negative electrode active material layer 22 may be suppressed or reduced despite changes in volume and / or relative position of the negative electrode active material layer 22 during the charge / discharge process. For example, when the negative electrode active material layer 22 does not include a binder, the negative electrode active material layer 22 may be easily separated from the negative electrode collector 21. When a portion of the separated negative electrode collector 21 is thus exposed, the exposed portion of the negative electrode collector 21 may contact the second solid electrolyte layer 23, and this may increase the possibility of a short circuit. The negative electrode active material layer 22 may be prepared by, for example, coating the negative electrode collector 21 with a slurry in which a material constituting the negative electrode active material layer 22 is dispersed, and drying the slurry and the negative electrode collector 21. When the binder is included in the negative electrode active material layer 22, the negative electrode active material may be stably dispersed in the slurry. For example, when the negative electrode current collector 21 is coated with the slurry using the screen printing method, clogging of the screen (eg, clogging by the accumulation of the negative electrode active material) may be suppressed or reduced.
[0116] Negative electrode layer: additives
[0117] The negative electrode active material layer 22 may further include additives (eg, fillers, coating agents, dispersants, and / or ion conductive agents) used in all-solid-state secondary batteries in the related art.
[0118] The negative electrode active material layer 22 may be Figure 4 The first negative electrode active material layer 22a shown in FIG. Figure 5 The third negative electrode active material layer 22b is shown in FIG.
[0119] Negative electrode layer: first negative electrode active material layer
[0120] The thickness of the first negative electrode active material layer 22a may be, for example, about 50% or less, about 40% or less, about 30% or less, about 20% or less, about 10% or less, or about 5% or less of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22a may be, for example, in the range of about 1 μm to about 20 μm, about 2 μm to about 10 μm, or about 3 μm to about 7 μm. When the thickness of the first negative electrode active material layer 22a is within these ranges, the cycle characteristics of the all-solid-state secondary battery 1 may be excellent or suitable, and the charge capacity of the first negative electrode active material layer 22a may be excellent or suitable. The charge capacity of the first negative electrode active material layer 22a may be, for example, about 50% or less, about 30% or less, about 10% or less, about 5% or less, or about 2% or less of the charge capacity of the positive electrode active material layer 12. The charge capacity of the first negative electrode active material layer 22a may be, for example, in the range of about 0.1% to about 50%, about 0.1% to about 30%, about 0.1% to about 10%, about 0.1% to about 5%, or about 0.1% to about 2% of the charge capacity of the positive electrode active material layer 12. When the charge capacity of the first negative electrode active material layer 22a is within these ranges, the thickness of the first negative electrode active material layer 22a may be controlled or selected to an appropriate or suitable range, and thus in repeated charge / discharge processes, the cycle characteristics and / or energy density of the all-solid-state secondary battery 1 may be excellent or suitable.
[0121] The charge capacity of the positive active material layer 12 can be obtained by multiplying the charge capacity density (mAh / g) of the positive active material in the positive active material layer 12 by the weight of the positive active material. When different positive active materials are used, the charge capacity density of each positive active material layer can be multiplied by its respective weight, and the sum of the products can be calculated to obtain the charge capacity of the positive active material layer 12. The charge capacity of the first negative active material layer 22a can be calculated in the same manner. For example, the charge capacity of the first negative active material layer 22a can be obtained by multiplying the charge capacity density (mAh / g) of the negative active material in the first negative active material layer by the weight of the negative active material. When different negative active materials are used, the charge capacity density of each negative active material layer can be multiplied by its respective weight, and the sum of the products can be calculated to obtain the charge capacity of the first negative active material layer 22a. Here, the charge capacity density of the positive active material and the negative active material is an estimated capacity obtained from an all-solid-state semi-single cell including lithium metal as a counter electrode. The charge capacity of the positive electrode active material layer 12 and the first negative electrode active material layer 22a can be directly measured by using the charge capacity measured by the all-solid semi-single cell. The measured charge capacity of each of the positive electrode active material and the negative electrode active material can be divided by the weight of the corresponding active material to calculate the charge capacity density. In some embodiments, the charge capacity of the positive electrode active material layer 12 and the first negative electrode active material layer 22a may be the initial charge capacity measured after the first charge cycle.
[0122] Negative electrode layer: Second negative electrode active material layer (precipitation layer)
[0123] In some embodiments, the all-solid-state secondary battery 1 may further include a second negative electrode active material layer between the negative electrode current collector 21 and the first negative electrode active material layer 22a by charging. The second negative electrode active material layer may be a metal layer including lithium or a lithium alloy. The metal layer may include lithium or a lithium alloy. Accordingly, because the second negative electrode active material layer is a metal layer including lithium, the second negative electrode active material layer can be used as, for example, a lithium storage device. The lithium alloy may be, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, or a Li-Si alloy, but the embodiment is not limited thereto, and any material that can be used as a lithium alloy in the art can be used. The second negative electrode active material layer may be formed of one of these alloys or lithium or may be formed of one or more suitable alloys.
[0124] The thickness of the second negative electrode active material layer may be, for example, in the range of about 1 μm to about 1000 μm, about 1 μm to about 500 μm, about 1 μm to about 200 μm, about 1 μm to about 150 μm, about 1 μm to about 100 μm, or about 1 μm to about 50 μm, but the embodiment is not limited thereto. When the second negative electrode active material layer is too thin, the second negative electrode active material layer may not be used as a lithium storage device. When the thickness of the second negative electrode active material layer is within these ranges, the cycle characteristics of the all-solid-state secondary battery 1 may be excellent or suitable. The second negative electrode active material layer may be, for example, a metal foil having a thickness within these ranges.
[0125] In the all-solid-state secondary battery 1, after the assembly of the all-solid-state secondary battery 1, the second negative electrode active material layer may be, for example, precipitated between the negative electrode collector 21 and the first negative electrode active material layer 22a by charging. When the second negative electrode active material layer is precipitated by charging after the assembly of the all-solid-state secondary battery 1, the second negative electrode active material layer is not present during the assembly of the all-solid-state secondary battery 1, and thus the all-solid-state secondary battery 1 may have an increased energy density. For example, the all-solid-state secondary battery 1 may be charged to exceed the charging capacity of the first negative electrode active material layer 22a. For example, the first negative electrode active material layer 22a may be overcharged. In the initial charging stage, lithium may be absorbed into the first negative electrode active material layer 22a. The negative electrode active material in the first negative electrode active material layer 22a may form an alloy or compound with lithium ions that have moved from the positive electrode layer 10. When the first negative electrode active material layer 22a is overcharged, for example, lithium may be precipitated on the rear surface of the first negative electrode active material layer 22a, for example, between the negative electrode current collector 21 and the first negative electrode active material layer 22a, and thus a metal layer corresponding to the second negative electrode active material layer is formed by the precipitated lithium. The second negative electrode active material layer may be a metal layer including lithium (ie, metallic lithium) as a main component. This can be attributed to the fact that, for example, the negative electrode active material in the first negative electrode active material layer 22a includes a material capable of forming an alloy or a compound with lithium. During discharge, the first negative electrode active material layer 22a and the second negative electrode active material layer, for example, lithium in the lithium metal layer, may be ionized and then move toward the positive electrode layer 10. Accordingly, lithium may be used as a negative electrode active material in the all-solid-state secondary battery 1. And, because the first negative electrode active material layer 22a coats the second negative electrode active material layer, the first negative electrode active material layer 22a may be used as a protective layer of the second negative electrode active material layer and simultaneously suppress or reduce the precipitation and growth of lithium dendrites. Therefore, a short circuit and / or a reduction in capacity of the all-solid-state secondary battery 1 can be suppressed or reduced, and thereby the cycle characteristics of the all-solid-state secondary battery 1 can be improved. Also, after the assembly of the all-solid-state secondary battery 1, when the second negative electrode active material layer is provided by charging, the negative electrode collector 21, the first negative electrode active material layer 22a, and the region between the negative electrode collector 21 and the first negative electrode active material layer 22a may be, for example, a Li-free region that does not include lithium (Li) in the initial state or the discharge state of the all-solid-state secondary battery 1.
[0126] Negative electrode layer: the third negative electrode active material layer
[0127] In the all-solid-state secondary battery 1 according to the embodiment, the negative electrode layer 20 may include a negative electrode current collector 21 and a third negative electrode active material layer 22 b on the negative electrode current collector 21 .
[0128] The third negative electrode active material layer 22b may be a metal layer including lithium or a lithium alloy. The metal layer may include lithium or a lithium alloy. Accordingly, because the third negative electrode active material layer 22b is a metal layer including lithium, the third negative electrode active material layer 22b may be used as, for example, a lithium storage device. The lithium alloy may be, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, or a Li-Si alloy, but the embodiment is not limited thereto, and any material that can be used as a lithium alloy in the art may be used. The third negative electrode active material layer 22b may be formed of one of these alloys or lithium or may be formed of one or more suitable alloys.
[0129] The thickness of the third negative electrode active material layer 22b may be, for example, in the range of about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 1 μm to about 30 μm, about 1 μm to about 15 μm, about 1 μm to about 10 μm, or about 3 μm to about 7 μm, but the embodiment is not limited thereto. When the thickness of the third negative electrode active material layer 22b is within these ranges, the third negative electrode active material layer 22b can be well used as a lithium storage device, and the cycle characteristics of the all-solid-state secondary battery 1 can be excellent or suitable without increasing weight and volume. The third negative electrode active material layer 22b may be, for example, a metal deposition layer or a metal foil having a thickness within these ranges.
[0130] In some embodiments, the lithium halide layer 24 may be additionally arranged on the third negative electrode active material layer 22b. The lithium halide layer 24 may be used as a passivation layer and thus may prevent or reduce degradation of the third negative electrode active material layer 22b. Because the lithium halide layer 24 is a high strength layer and a high hardness layer, the lithium halide layer 24 may be a protective layer for protecting the third negative electrode active material layer 22b. The lithium halide layer 24 may include at least one selected from LiF, LiCl, LiBr, and LiI, and, for example, the lithium halide layer 24 may be a LiF layer. The lithium halide layer 24 may be arranged on the third negative electrode active material layer 22b by deposition. The thickness of the lithium halide layer 24 may be, for example, in the range of about 10 μm to about 300 μm, about 10 μm to about 150 μm, about 10 μm to about 90 μm, about 10 μm to about 60 μm, or about 20 μm to about 50 μm, but the embodiment is not limited thereto. When the thickness of the lithium halide layer 24 is within these ranges, the lithium halide layer 24 can prevent or reduce degradation of the third negative electrode active material layer 22 b , and can improve the energy density of the all-solid-state secondary battery 1 .
[0131] In some embodiments, the carbon layer 25 may be additionally disposed on Figure 4 The first negative electrode active material layer 22a and the second solid electrolyte layer 23 shown in FIG. Figure 5Between the third negative electrode active material layer 22b and the second solid electrolyte layer 23 shown in FIG. Figure 5 As shown in FIG. 2 , the carbon layer 25 may be between the lithium halide layer 24 and the second solid electrolyte layer 23 .
[0132] The thickness of the carbon layer 25 may be, for example, in the range of about 1 μm to about 10 μm, about 2 μm to about 10 μm, or about 1 μm to about 5 μm. When the thickness of the carbon layer 25 is within these ranges, the interface resistance can be effectively reduced, and the energy density of the all-solid-state secondary battery 1 can be improved. The carbon layer 25 may include a binder and a carbon-based material. The carbon-based material may be or include amorphous carbon or crystalline carbon. The binder may be or include a binder used in the above-mentioned positive electrode layer 10. The carbon layer 25 may be or include (for example, at the same time) amorphous carbon and crystalline carbon. The weight ratio of amorphous carbon to crystalline carbon in the carbon layer 25 may be, for example, in the range of about 4:6 to about 6:4.
[0133] Negative electrode layer: negative electrode current collector
[0134] For example, the negative electrode current collector 21 may be formed of a material that can react with lithium to form an alloy or a compound. Examples of the material of the negative electrode current collector 21 may include copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni), but the embodiment is not limited thereto, and any material that can be used as an electrode current collector in the art may be used. The negative electrode current collector 21 may be formed of a coating material of one of the examples of the metal or alloy or at least two metals selected from the examples. The negative electrode current collector 21 may be, for example, in the form of a plate or foil.
[0135] The all-solid-state secondary battery 1 may further include a thin film on the negative electrode collector 21, the thin film including an element that can form an alloy with lithium. The thin film may be provided between the negative electrode collector 21 and the first negative electrode active material layer 22a. The thin film may include, for example, an element that can form an alloy with lithium. Examples of elements that can form an alloy with lithium may include gold, silver, zinc, tin, indium, silicon, aluminum and / or bismuth, but the embodiment is not limited thereto, and any element that can form an alloy with lithium in the art may be used. The thin film may be formed of an alloy of one or two or more of these metals. When the thin film is provided on the negative electrode collector 21, for example, the second negative electrode active material layer precipitated between the thin film and the first negative electrode active material layer 22a may be further flattened, and thus the cycle characteristics of the all-solid-state secondary battery 1 may be further improved.
[0136] The thickness of the film may be, for example, in the range of about 1 nm to about 800 nm, about 50 nm to about 600 nm, or about 100 nm to about 500 nm. When the thickness of the film is within these ranges, the function of the film can be easily demonstrated. As a result, the film itself absorbs lithium, and therefore the amount of lithium precipitation in the negative electrode layer 20 can be reduced, which can improve the cycle characteristics of the all-solid-state secondary battery 1 without reducing the energy density of the all-solid-state secondary battery 1. The film may be, for example, deposited on the negative electrode collector 21 by vacuum vapor deposition, sputtering or electroplating.
[0137] According to another embodiment, the reference Figure 2A and Figure 2B A method for preparing an all-solid-state secondary battery is described.
[0138] First, if Figure 2A , the insulating member 31 is arranged on the outer peripheral portion of the second solid electrolyte layer 23 on which the negative electrode layer 20 (e.g., 21+22) is laminated, and then the composite solid electrolyte 30 is arranged on the central portion of the second solid electrolyte layer 23. Since both surfaces (e.g., the top plane and the bottom plane) of the insulating member 31 are coated with a thermoplastic adhesive film, the insulating member 31 can have excellent or suitable adhesive strength to the composite solid electrolyte 30, the second solid electrolyte layer 23, and the first solid electrolyte layer 13.
[0139] The composite solid electrolyte 30 can be prepared by coating and drying a composition including an ion conductor, a lithium salt, a binder and an organic solvent on a substrate and heat treating the resultant. The composition may further include an ionic liquid. The composition may be separated from the substrate as a film, and thus a composite solid electrolyte in the form of a self-supporting film can be obtained.
[0140] The positive electrode active material layer 12 is disposed on the positive electrode current collector 11 to prepare the positive electrode layer 10 .
[0141] Layer Figure 2A The order shown in is laminated in sequence and then pressed to prepare an all-solid-state secondary battery. The pressing process may be carried out at a pressure ranging from about 100 MPa to about 700 MPa, about 200 MPa to about 600 MPa, or about 300 MPa to about 550 MPa, or about 500 MPa, and at a temperature ranging from about 30°C to about 95°C, about 50°C to about 90°C, or about 80°C to about 90°C. When a pressing process is required in the preparation of an all-solid-state secondary battery according to an embodiment, a pressing process may be carried out under these conditions.
[0142] The method of preparing an all-solid-state secondary battery may include coating and pressing a positive active material layer 12 on a positive current collector 11 and then coating and pressing a first solid electrolyte layer 13 on the positive active material layer 12 and the positive current collector 11 to prepare a first solid electrolyte layer 13 / positive electrode layer 10 laminate.
[0143] Separately, the method may further include coating and pressing the negative electrode active material layer 22 on the negative electrode collector 21 and then coating and pressing the second solid electrolyte layer 23 on the negative electrode active material layer 22 and the negative electrode collector 21 to prepare a second solid electrolyte layer 23 / negative electrode layer 20 laminate.
[0144] The insulating member 31 is attached to the second solid electrolyte layer 23 of the second solid electrolyte layer 23 / negative electrode layer 20 laminate, and then the composite solid electrolyte 30 is coated on the resultant to complete the composite structure. Next, the composite solid electrolyte 30 is combined with the first solid electrolyte layer 13 / positive electrode layer 10 laminate to prepare a desired or suitable all-solid-state secondary battery.
[0145] In some embodiments, by arranging the composite solid electrolyte 30 of the composite structure so that it has increased contact with the first solid electrolyte layer 13 on the positive electrode layer 10 compared to the second solid electrolyte layer 23 on the negative electrode layer 20, the occurrence of a short circuit caused by lithium dendrites can be prevented or reduced in advance.
[0146] exist Figure 2B In the embodiment, the length L1 of the insulating member 31 may be in the range of about 0.5 mm to about 1.5 mm or about 0.5 mm to about 1.2 mm, and the length L2 of the insulating member 31 may be in the range of about 0.5 mm to about 3.0 mm. When the lengths L1 and L2 are within these ranges, the occurrence of short circuits can be effectively suppressed or reduced without reducing the capacity of the positive electrode. When the length L1 is longer than these ranges, the insulating member 31 may invade the area of the positive electrode, and thus the capacity of the battery may be reduced.
[0147] The characteristics of the all-solid-state secondary battery 1 may be changed according to the length L1 of the insulating member 31. When the length L1 increases, the physical short circuit of the all-solid-state secondary battery 1 can be reduced, and the single cell stability of the all-solid-state secondary battery 1 can be increased. However, as the insulating member 31 invades the area of the positive electrode, the capacity of the positive electrode can be reduced. The length L1 may be small or appropriately controlled to reduce the reduction in the capacity of the positive electrode. When the length L1 is 0 mm, the reduction in the capacity of the positive electrode may not occur, but the physical short circuit may not be prevented or reduced. Therefore, it is necessary to optimize the lengths L1 and L2 based on preventing or reducing the reduction in the capacity of the positive electrode and / or the physical short circuit.
[0148] One or more embodiments will now be described in more detail with reference to examples. However, these examples are not intended to limit the scope of one or more embodiments.
[0149] Example 1
[0150] Preparation of negative electrode layer
[0151] A stainless steel (SUS) foil having a thickness of about 10 μm was prepared as a negative electrode current collector, and carbon black (CB) having a primary particle size of about 30 nm and silver (Ag) particles having an average particle size of about 60 nm were prepared as negative electrode active materials.
[0152] 0.25 g of a mixture powder prepared by mixing carbon black (CB) and silver (Ag) particles in a weight ratio of 3: 1 was placed in a container, and 2 g of an NMP solution including about 7 weight % (wt %) of a PVDF binder (#9300 available from Kureha Co.) was added to the container to prepare a mixture solution. Next, the mixture solution was stirred while NMP was gradually added to the mixture solution to prepare a slurry. The slurry thus prepared was applied to a SUS foil using a bar coater and dried in a convection constant temperature oven at about 80° C. for about 10 minutes to obtain a laminate. The laminate was vacuum dried at a temperature of about 40° C. for about 10 hours. By these processes, a negative electrode layer including a first negative electrode active material layer prepared on a negative electrode collector was prepared.
[0153] Preparation of solid electrolyte layer
[0154] An acrylic binder (SX-A334, Zeon Co., Ltd.) was added to octyl acetate to prepare a 4 wt % binder solution. The acrylic binder solution was added to Li 6 PS 5 Cl solid electrolyte (D50 = 3 μm, crystalline), which is a argyrodite type or quasi-crystal, and mixed using a Thinky mixer to prepare a slurry. Based on 98.5 parts by weight of the solid electrolyte, the slurry includes about 1.5 parts by weight of an acrylic binder. The slurry is applied to a non-woven fabric using a bar coater and dried in a convection oven at about 80°C for about 10 minutes to obtain a laminate. The laminate is vacuum dried at a temperature of about 70°C for about 2 hours. By these processes, a solid electrolyte layer is prepared. The solid electrolyte layer is used as a first solid electrolyte layer and a second solid electrolyte layer.
[0155] Preparation of negative electrode layer / second solid electrolyte layer laminate
[0156] The second solid electrolyte layer (SE2) is arranged on the first negative electrode active material layer of the negative electrode layer to prepare a laminate. The laminate is hot plate pressed at a temperature of about 90°C and a pressure of about 500MPa for about 10 minutes to prepare a negative electrode layer / second solid electrolyte layer laminate. Because the solid electrolyte layer is sintered by the pressing process, the battery characteristics of the all-solid-state secondary battery are improved. The thickness of the sintered negative electrode layer / second solid electrolyte layer laminate is about 45μm. The thickness of the pressed first negative electrode active material layer is about 7μm.
[0157] Preparation of positive electrode layer
[0158] LiNi 0.8 Co 0.15 Mn 0.05 O 2 (NCM) was prepared as the positive electrode active material. 6 PS 5 Cl solid electrolyte (D50 = 0.6 μm, crystalline), which is argyrodite type or quasi-crystal, is used as the solid electrolyte. A polytetrafluoroethylene (PTFE) binder (manufactured by DuPont) Binder) was prepared as a binder. Carbon black (CB) and carbon nanofibers (CNF) (nanotubes) were prepared as conductive agents. These materials were mixed in a weight ratio of positive active material: solid electrolyte: carbon black: carbon nanotubes: binder = 85.5:10:1.5:1.5:1.5, and the mixture was added to xylene as a solvent to prepare a positive active material composition. The positive active material composition was mixed using a mixing grinder, kneaded at 80°C using a heated kneader, molded into a sheet form, and vacuum dried at 40°C for 8 hours to prepare a positive electrode layer, which includes a positive electrode collector and a positive active material layer on the positive electrode collector. Aluminum foil was used as a positive electrode collector.
[0159] Preparation of positive electrode layer / first solid electrolyte layer laminate
[0160] The first solid electrolyte layer is arranged on the positive electrode layer to prepare a laminate. The laminate is hot plate pressed at a temperature of about 90°C and a pressure of about 500MPa for about 10 minutes to prepare a positive electrode layer / first solid electrolyte layer laminate. Because the solid electrolyte layer is sintered by the pressing process, the battery characteristics of the all-solid-state secondary battery are improved. The thickness of the negative electrode layer / second solid electrolyte layer laminate after sintering is about 45μm. The thickness of the pressed positive electrode active material layer is about 100μm.
[0161] The insulating member is on the outer periphery and the end region of the upper part of the negative electrode layer / second solid electrolyte layer laminate. An insulating polypropylene film (having a thickness of 5 μm, available from SKI) is used as the insulating member. d, L1 and L2 of the insulating member are controlled or selected according to the conditions shown in Table 1.
[0162] Next, the composite solid electrolyte SEC is arranged on the central portion of the negative electrode layer / second solid electrolyte layer laminate, and the insulating member is arranged on the outer periphery of the second solid electrolyte layer to prepare a composite structure. Subsequently, the positive electrode layer / first solid electrolyte layer (SE1) laminate is laminated on the composite structure.
[0163] The laminate thus prepared through these processes was hot plate pressed at a temperature of about 90° C. and a pressure of about 500 MPa for about 1 minute. After the pressing process, punching was performed on the resultant, and one end was attached to a current collector, thereby completing the preparation of an all-solid-state secondary battery.
[0164] A self-supporting film prepared as follows was used as a composite solid electrolyte.
[0165] First, 1.38 g of PVDF (Solef 5130) as a binder was dissolved in 13.4 mL of NMP as a solvent, 0.75 g of LiTFSI as a lithium salt was added thereto, and then 2.07 g of PEO (600,000 g / mol) was added thereto to obtain a mixture. The mixture was stirred at room temperature (25° C.) overnight, and after the mixture was applied to a substrate, it was dried in a convection oven at about 80° C., and vacuum dried at 120° C. for 6 hours to obtain a self-supporting composite solid electrolyte (PEO-LiTFSI (SEC) layer).
[0166] Examples 2 to 9
[0167] All-solid-state secondary batteries were each prepared in substantially the same manner as in Example 1, except that the conditions of the insulating member and the composite solid electrolyte SEC were changed to those shown in Table 1.
[0168] Comparative Example 1
[0169] Preparation of negative electrode layer
[0170] A SUS foil having a thickness of about 10 μm was prepared as a negative electrode current collector, and carbon black (CB) having a primary particle size of about 30 nm and silver (Ag) particles having an average particle size of about 60 nm were prepared as negative electrode active materials.
[0171] 0.25 g of a mixture powder prepared by mixing carbon black (CB) and silver (Ag) particles in a weight ratio of 3: 1 was placed in a container, and 2 g of an NMP solution including about 7 weight % (wt %) of a PVDF binder (#9300 available from Kureha Co.) was added to the container to prepare a mixture solution. Next, the mixture solution was stirred while NMP was gradually added to the mixture solution to prepare a slurry. The prepared slurry was applied to a SUS foil using a bar coater and dried in a convection constant temperature oven at about 80°C for about 10 minutes to obtain a laminate. The laminate was vacuum dried at a temperature of about 40°C for about 10 hours. By these processes, a negative electrode layer including a first negative electrode active material layer prepared on a negative electrode collector was prepared.
[0172] Preparation of solid electrolyte layer
[0173] An acrylic binder (SX-A334, Zeon Co., Ltd.) was added to octyl acetate to prepare a 4 wt % binder solution. The acrylic binder solution was added to Li 6 PS 5 Cl solid electrolyte (D50 = 3 μm, crystalline), which is argyrodite type or quasi-crystal, and mixed using a Thinky mixer to prepare a slurry. Based on 98.5 parts by weight of the solid electrolyte, the slurry includes about 1.5 parts by weight of an acrylic binder. The slurry is applied to a non-woven fabric using a bar coater and dried in a convection oven at about 80°C for about 10 minutes to obtain a laminate. The laminate is vacuum dried at a temperature of about 70°C for about 2 hours. By these processes, a solid electrolyte layer is prepared.
[0174] Preparation of positive electrode layer
[0175] LiNi 0.8 Co 0.15 Mn 0.05 O 2 (NCM) was prepared as the positive electrode active material. 6 PS 5 Cl solid electrolyte (D50 = 0.6 μm, crystalline), which is argyrodite type or quasi-crystal, is used as the solid electrolyte. A polytetrafluoroethylene (PTFE) binder (manufactured by DuPont) Binder) was prepared as a binder. Carbon black (CB) and carbon nanofibers (CNF) (nanotubes) were prepared as conductive agents. These materials were mixed in a weight ratio of positive active material: solid electrolyte: carbon black: carbon nanotubes: binder = 85.5:10:1.5:1.5:1.5, and the mixture was added to xylene as a solvent to prepare a positive active material composition. The positive active material composition was mixed using a mixing grinder, kneaded at 80°C using a heated kneader, molded into a sheet form, and vacuum dried at 40°C for 8 hours to prepare a positive electrode layer, which includes a positive electrode collector and a positive electrode active material layer on the positive electrode collector. Aluminum foil was used as a positive electrode collector.
[0176] The solid electrolyte layer is arranged on the positive electrode layer and pressed at a temperature of about 90°C and a pressure of about 500 MPa for about 10 minutes, and the negative electrode layer is arranged on the resultant to prepare a laminate. The laminate is hot plate pressed at a temperature of about 90°C and a pressure of about 500 MPa for about 10 minutes, thereby completing the preparation of an all-solid-state secondary battery.
[0177] Comparative Example 2
[0178] Solid electrolyte layer SE was arranged on the cathode layer prepared in Comparative Example 1 to prepare a cathode layer / solid electrolyte layer laminate. The laminate was hot plate pressed at a temperature of about 90° C. and a pressure of about 500 MPa for about 10 minutes to prepare a cathode layer / solid electrolyte layer laminate.
[0179] The negative electrode layer prepared in Comparative Example 1 was laminated on the solid electrolyte layer of the positive electrode layer / solid electrolyte layer laminate to prepare an all-solid secondary battery.
[0180] Comparative Example 3
[0181] Solid electrolyte layer SE was arranged on the first negative electrode active material layer of the negative electrode layer of Comparative Example 1 to prepare a laminate. The laminate was hot plate pressed at a temperature of about 90° C. and a pressure of about 500 MPa for about 10 minutes to prepare a negative electrode layer / solid electrolyte layer laminate.
[0182] The positive electrode layer prepared in Comparative Example 1 was laminated on the solid electrolyte layer of the negative electrode layer / solid electrolyte layer laminate to prepare an all-solid-state secondary battery.
[0183] Comparative Example 4
[0184] An all-solid-state secondary battery was prepared in substantially the same manner as in Example 1, except that the process of arranging the composite solid electrolyte SEC and the insulating member on the top surface center portion of the upper portion of the negative electrode layer / second solid electrolyte layer laminate was omitted and the conditions were changed to those shown in Table 1.
[0185] Comparative Example 5
[0186] An all-solid-state secondary battery is prepared in substantially the same manner as in Example 1, except that (only) the insulating member is arranged on the outer periphery of the upper portion of the negative electrode layer / second solid electrolyte layer laminate, and the first solid electrolyte layer / positive electrode layer laminate is laminated thereon according to the conditions shown in Table 1.
[0187] Comparative Example 6
[0188] An all-solid-state secondary battery is prepared in substantially the same manner as in Example 1, except that the composite solid electrolyte is (only) arranged on the entire top surface of the upper portion of the negative electrode layer / second solid electrolyte layer laminate, and the first solid electrolyte layer / positive electrode layer laminate is laminated thereon according to the conditions shown in Table 1.
[0189] Comparative Example 7
[0190] An all-solid-state secondary battery is prepared in substantially the same manner as in Example 1, except that the composite solid electrolyte and the insulating member are each arranged in sequence on the entire top surface of the upper portion of the negative electrode layer / second solid electrolyte layer laminate, and the first solid electrolyte layer / positive electrode layer laminate is laminated thereon according to the conditions shown in Table 1.
[0191] Table 1
[0192]
[0193] In Table 1, the sum of S1, S2 and S3 is selected as 100% (for example, except for Comparative Example 5, which omits the composite solid electrolyte, and Comparative Example 7, in which the composite solid electrolyte and the insulating member are each sequentially arranged on the entire top surface of the upper portion of the negative electrode layer).
[0194] In Table 1, area S1 represents the total area of the SEC layer and the insulating member. Figure 3 The area of the SEC layer in FIG. 1 , and the areas S2 and S3 represent the total area of the SEC layer and the insulating member, respectively. Figure 3 The areas of the insulating members are S2 and S3.
[0195] otherwise, Figure 3 The area S1 is based on the total area of the second solid electrolyte layer, and Figure 3 The areas S2 and S3 are based on the total area of the second solid electrolyte layer.
[0196] Evaluation Example 1: Charge / Discharge Test
[0197] The charge / discharge characteristics of the all-solid-state secondary batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 7 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid-state secondary batteries in a thermostat at 60°C.
[0198] The battery was charged for about 10 hours with a constant current of 0.1 C and a cutoff current of 0.05 C until the battery voltage was 4.25 V, and then discharged for about 10 hours with a constant current of 0.1 C until the battery voltage was 2.5 V ("first cycle").
[0199] Subsequently, the battery was charged for about 10 hours with a constant current of 0.1 C and a cutoff current of 0.05 C until the battery voltage was 4.25 V, and then discharged for about 3 hours with a constant current of 0.33 C until the battery voltage was 2.5 V ("second cycle").
[0200] Thereafter, the battery was charged for about 10 hours with a constant current of 0.1 C and a cutoff current of 0.05 C until the battery voltage was 4.25 V. Then, the battery was discharged for about 1 hour with a constant current of 1.0 C until the battery voltage was 2.5 V ("third cycle").
[0201] Next, the battery was charged for about 3 hours with a constant current of 0.33 C and a cutoff current of 0.1 C until the battery voltage was 4.25 V. Then, the battery was discharged for about 3 hours with a constant current of 0.33 C until the battery voltage was 2.5 V ("the fourth cycle").
[0202] The high rate characteristic of each battery was expressed as a percentage value of the discharge capacity measured at 1 C relative to the discharge capacity at 0.33 C (1 C / 0.33 C).
[0203] And, the occurrence of short circuit of each battery was evaluated, and the results are shown in Table 2. Short circuit occurring during the initial charge is indicated by "○", short circuit occurring after the second cycle is indicated by "△", and short circuit not occurring is indicated by "×".
[0204] Table 2
[0205]
[0206]
[0207] The all-solid-state secondary batteries of Examples 1 to 9 had no short circuit occurring after fabrication and had excellent or suitable rate performance.
[0208] The all-solid-state secondary battery of Comparative Example 1 is a single cell prepared by pressing and punching a negative electrode layer / SE layer / positive electrode layer laminate. During the punching process, physical defects occurred at the edge of the laminate, the initial capacity decreased due to short circuit, and therefore the high rate characteristics of the battery could not be evaluated.
[0209] The all-solid-state secondary battery of Comparative Example 2 is a single cell prepared by pressing, stamping and laminating the negative electrode layer and the SE layer / positive electrode layer, respectively. Because of the physical defects occurring at the edge of the SE layer / positive electrode layer, a short circuit occurs during the initial charge, and the interface resistance between the negative electrode layer and the SE layer is high, which reduces the initial capacity of the battery.
[0210] The all-solid-state secondary battery of Comparative Example 3 is a single cell prepared by pressing, stamping and laminating the SE layer / negative electrode layer and the positive electrode layer, respectively. Although better than those of the all-solid-state secondary battery of Comparative Example 2, the all-solid-state secondary battery of Comparative Example 3 has an increased interface resistance of the SE layer / positive electrode layer and a reduced initial discharge capacity due to physical defects at the edge of the SE layer / negative electrode layer, and the high rate characteristics of the battery cannot be evaluated due to the occurrence of a short circuit.
[0211] The all-solid-state secondary battery of Comparative Example 4 is a single cell prepared by pressing, stamping and laminating the SE layer / negative electrode layer and the SE layer / positive electrode layer, respectively. Compared with Comparative Examples 2 and 3, the all-solid-state secondary battery of Comparative Example 4 has a low interface resistance of the SE layer / positive electrode layer and an interface resistance of the SE layer / negative electrode layer. However, the all-solid-state secondary battery of Comparative Example 4, while having a reduced interface resistance of the SE layer / negative electrode layer and a reduced interface resistance of the SE layer / positive electrode layer, still has a high interface resistance of the two SE layers, an initial capacity reduced by a short circuit caused by a physical defect at the edge of the battery, and the high rate characteristics cannot be evaluated.
[0212] The all-solid-state secondary battery of Comparative Example 5 is a single cell prepared by applying an insulating member to improve physical defects at the edge of the battery of Comparative Example 4. Therefore, the occurrence of short circuits in the all-solid-state secondary battery in Comparative Example 5 is reduced, but the initial capacity of the battery is insufficient due to the interface resistance between the two SE layers.
[0213] A short circuit occurred in the all-solid-state secondary battery of Comparative Example 6, and the high-rate characteristics could not be evaluated. A short circuit did not occur in the all-solid-state secondary battery of Comparative Example 7, but the initial capacity and high-rate characteristics of the battery were deteriorated compared to those of the all-solid-state secondary batteries of Examples 1 to 9.
[0214] According to an embodiment, an all-solid-state secondary battery includes a composite solid electrolyte and an insulating member, and thus a short circuit in the battery may be prevented or reduced, and the all-solid-state secondary battery may have improved cycle characteristics.
[0215] As used herein, the terms "substantially," "about," and similar terms are used as terms of approximation and not as terms of degree, and are intended to take into account the inherent deviations of measured or calculated values that one of ordinary skill in the art would recognize. Taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system), "about" or "approximately" as used herein include the recited value and mean within the range of acceptable deviation as determined by one of ordinary skill in the art for the particular value. For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the recited value.
[0216] Any numerical range listed herein is intended to include all subranges of the same numerical precision included in the listed range. For example, the range of "1.0 to 10.0" is intended to include all subranges between the listed minimum value 1.0 and the listed maximum value 10.0 (and including the end value), that is, all subranges with a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4 to 7.6. Any maximum numerical limit listed herein is intended to include all lower numerical limits included therein, and any minimum numerical limit listed in this specification is intended to include all higher numerical limits included therein. Therefore, the applicant reserves the right to modify this specification (including claims) to explicitly list any subranges included in the range explicitly listed herein.
[0217] It should be understood that the embodiments described herein should be considered as illustrative only and not for limiting purposes. The description of features or aspects in each embodiment should generally be considered as being applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, it will be understood by those of ordinary skill in the art that various changes can be made in form and detail without departing from the spirit and scope defined by the appended claims and their equivalents.
Claims
1. An all-solid-state secondary battery, comprising: positive electrode layer; Negative electrode layer; a first solid electrolyte layer between the positive electrode layer and the negative electrode layer and adjacent to the positive electrode layer; and a second solid electrolyte layer between the positive electrode layer and the negative electrode layer and adjacent to the negative electrode layer, The positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector. The negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer or a third negative electrode active material layer on the negative electrode current collector, and a composite structure between the first solid electrolyte layer and the second solid electrolyte layer, and The composite structure comprises: a composite solid electrolyte on a central portion of the second solid electrolyte layer and including an ion conductor and a lithium salt; and an insulating member on an outer peripheral portion of the second solid electrolyte layer and around one or more outer surfaces of the composite solid electrolyte, wherein the insulating member is at least one selected from an insulating polymer and an insulating inorganic material, The total area of the composite solid electrolyte is in the range of 70% to 95% of the corresponding total area of the second solid electrolyte layer.
2. The all-solid-state secondary battery according to claim 1, wherein the ion conductor of the composite solid electrolyte comprises polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polystyrene-acrylonitrile copolymer, polyvinyl chloride, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene vinyl acetate copolymer or a combination thereof. 3 . The all-solid-state secondary battery according to claim 1 , wherein the composite solid electrolyte further comprises at least one selected from a binder and an ionic liquid.
4. The all-solid-state secondary battery according to claim 1, wherein the lithium salt is at least one selected from the group consisting of LiPF6, LiBF4, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)3C, LiC2F5SO3, Li(FSO2)2N, LiC4F9SO3, LiN(SO2CF2CF3)2, LiN(CN)2, and compounds represented by Formula 1 to Formula 4: 5 . The all-solid-state secondary battery according to claim 1 , wherein the insulating member comprises polypropylene, acrylonitrile-butadiene rubber, styrene butadiene rubber, isobutylene isoprene rubber, chloroprene rubber, ethylene propylene diene monomer, or a combination thereof. 6 . The all-solid-state secondary battery according to claim 1 , wherein a thermoplastic adhesive coating film is located on at least one surface of the insulating member. 7 . The all-solid secondary battery according to claim 1 , wherein a total exposed area of the insulating member is in a range of 5% to 60% of a corresponding total area of the second solid electrolyte layer. 8 . The all-solid secondary battery according to claim 1 , wherein the insulating member protrudes from an outermost portion of the second solid electrolyte layer.
9. The all-solid-state secondary battery according to claim 1, wherein the thickness of the composite solid electrolyte is in the range of 1 μm to 10 μm, and the thickness of the insulating member is in the range of 1 μm to 10 μm, wherein the thickness of the composite solid electrolyte is equal to or greater than the thickness of the insulating member. 10 . The all-solid-state secondary battery according to claim 1 , wherein the first solid electrolyte layer and the second solid electrolyte layer each independently include a sulfide-based solid electrolyte.
11. The all-solid-state secondary battery according to claim 10, wherein the sulfide-based solid electrolyte is at least one selected from the following: Li2S-P2S5, Li2S-P2S5-LiX, wherein X is a halogen, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , wherein m and n are each positive numbers, and Z is one of Ge, Zn and Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , wherein p and q are each positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In, Li 7-x PS 6-x Cl x , where 0≤x≤2, Li 7-x PS 6-x Br x , where 0≤x≤2 and Li 7-x PS 6-x I x , where 0≤x≤2. 12 . The all-solid-state secondary battery according to claim 11 , wherein the sulfide-based solid electrolyte is an argyrodite-type solid electrolyte including at least one selected from the group consisting of Li 6 PS 5 Cl, Li 6 PS 5 Br and Li 6 PS 5 I.
13. The all-solid-state secondary battery according to claim 1, wherein the first negative electrode active material layer comprises a negative electrode active material and a binder, and The negative electrode active material is in the form of particles, and the average particle size of the negative electrode active material is 4 μm or less.
14. The all-solid-state secondary battery according to claim 13, wherein the negative electrode active material comprises at least one selected from a carbon-based negative electrode active material and a metal or metalloid negative electrode active material, and The carbon-based negative electrode active material includes at least one selected from amorphous carbon and crystalline carbon. 15 . The all-solid-state secondary battery according to claim 14 , wherein the metal or metalloid negative electrode active material comprises at least one selected from the group consisting of gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin and zinc.
16. The all-solid-state secondary battery according to claim 13, wherein the negative electrode active material comprises a mixture of first particles and second particles, wherein the first particles comprise amorphous carbon, and the second particles comprise metal or metalloid, Wherein an amount of the second particles is in a range of 8 wt % to 60 wt % based on the total weight of the mixture.
17. The all-solid-state secondary battery according to claim 1, further comprising a second negative electrode active material layer, the second negative electrode active material layer is between the negative electrode collector and the first negative electrode active material layer, between the second solid electrolyte layer and the first negative electrode active material layer, or between the negative electrode collector and the first negative electrode active material layer and between the second solid electrolyte layer and the first negative electrode active material layer, and The second negative electrode active material layer includes lithium or a lithium alloy. 18 . The all-solid-state secondary battery according to claim 1 , wherein the third negative electrode active material layer is a metal layer including lithium or a lithium alloy.
Citation Information
Patent Citations
Apparatus and method for proviidng health care service in building
KR1020200109484A
Lithium metal electrode and its related lithium metal battery
CN107946541A
All-solid power storage device and method for manufacturing the same
JP2017117672A
Solid electrolyte membrane and all-solid-state battery comprising same
WO2019240547A1